Expanded Dengue Syndrome: A Comprehensive Review (Journal of Comilla Medical College Teachers' Association, 2026)
Background: Expanded Dengue Syndrome (EDS) encompasses a wide spectrum of atypical and severe clinical manifestations of dengue virus infection involving various organ systems beyond the classical definitions of dengue fever, dengue hemorrhagic fever, and dengue shock syndrome. Recognized by the World Health Organization, EDS includes neurological, hepatic, renal, cardiac, pulmonary, and hematological complications that may occur with or without plasma leakage. Increasing dengue incidence worldwide has led to a parallel rise in these unusual presentations, posing significant diagnostic and therapeutic challenges, particularly in endemic countries such as Bangladesh. This review summarizes current knowledge on the epidemiology, pathophysiology, clinical manifestations, diagnostic approach, management strategies, and prognosis of Expanded Dengue Syndrome, highlighting the importance of early recognition and multidisciplinary care to reduce morbidity and mortality.J Com Med Col Teachers’ Asso Jan 2026; 30(1): 63-65